Long-Term Outcome After Carotid Artery Stenting: A Population-Based Matched Cohort Study. Issue 8 (August 2016) - Jonsson, Magnus; Lindström, David; Gillgren, Peter; Wanhainen, Anders; Malmstedt, Jonas
Abstract : Background and Purpose—: Long-term outcome after carotid artery stenting (CAS), a less invasive technique than carotid endarterectomy (CEA), for prevention of stroke, is unclear. The aim was to assess long-term outcomes after CAS, compared with CEA, in a nationwide cohort study. Methods—: All patients registered in the national Swedish Vascular Registry (Swedvasc) treated with primary CAS between 2005 and 2012 were identified. For every CAS, 2 CEA controls, matched for sex, age, procedure year, and indication (symtomatic/asymtomatic), were chosen. Postoperative stroke was identified by cross-matching the cohort with the InPatient Registry and charts review. Primary end point was ipsilateral stroke or death >30 days postoperatively. Results—: A total of 1157 patients were included, 409 CAS and 748 CEA; 73% men with mean age 70 years and 69% were symptomatic. Risk factor profile was similar between the 2 groups. Median follow-up time was 4.1 years. Ipsilateral stroke or death of >30 days postoperatively occurred in 95 of 394 in the CAS group versus 120 of 724 in the CEA group (adjusted hazard ratio, 1.59; 95% confidence interval, 1.15–2.18). The corresponding adjusted rates for death, ipsilateral stroke of >30 days, and any stroke or death of >30 days were 25.7% versus 18.6% (hazard ratio, 1.20; 95% confidence interval, 0.84–1.72), 9.4% versus 2.9% (hazard ratio, 3.40; 95% confidence interval, 1.53–7.53), 34.2% versus 23.6% (hazard ratio, 1.49; 95% confidence interval, 1.10–2.00) for the CAS group versus CEA group, respectively. Conclusions—: In this nationwide cohort study, CAS was associated with an increased long-term risk of ipsilateral stroke and death during after the perioperative phase when compared with CEA. Abstract : Supplemental Digital Content is available in the text.